Are Treasury Securities Free of Default? - Nippani, Srinivas; Liu, Pu; Schulman, Craig T. (Journal of Financial and Quantitative Analysis, 2001)
Srinivas Nippani, Pu Liu, Craig T. Schulman, Are Treasury Securities Free of Default?, The Journal of Financial and Quantitative Analysis, Vol. 36, No. 2, Special Issue on International Corporate Governance (Jun., 2001), pp. 251-265